Ex 11.2

Ex 11.2, 1 (i)

Ex 11.2, 1 (ii) Important

Ex 11.2, 1 (iii)

Ex 11.2, 1 (iv) Important

Ex 11.2, 1 (v) Important

Ex 11.2, 1 (vi)

Ex 11.2, 1 (vii) Important

Ex 11.2, 1 (viii)

Ex 11.2, 1 (ix) Important

Ex 11.2, 1 (x)

Ex 11.2, 2 (i)

Ex 11.2, 2 (ii) Important

Ex 11.2, 2 (iii)

Ex 11.2, 2 (iv) Important

Ex 11.2, 2 (v)

Ex 11.2, 2 (vi) Important

Ex 11.2, 2 (vii)

Ex 11.2, 2 (viii) Important

Ex 11.2, 2 (ix) Important

Ex 11.2, 2 (x)

Ex 11.2, 2 (xi) Important

Ex 11.2, 2 (xii)

Ex 11.2, 3 (i) Important

Ex 11.2, 3 (ii)

Ex 11.2, 3 (iii) Important

Ex 11.2, 3 (iv) Important

Ex 11.2, 4 (i)

Ex 11.2, 4 (ii) Important

Ex 11.2, 4 (iii) Important

Ex 11.2, 4 (iv)

Ex 11.2, 5 (i) Important

Ex 11.2, 5 (ii)

Ex 11.2, 5 (iii) Important You are here

Last updated at April 16, 2024 by Teachoo

Ex 11.2, 5 Simplify: (iii) (3^5 × 〖10〗^5 × 25)/(5^7 ×〖 6〗^5 ) (3^5 × 〖10〗^5 × 25)/(5^7 ×〖 6〗^5 ) = (3^5 × (2 × 5)^5 × (5 × 5))/(5^7 × (2 × 3)^5 ) = (3^5× 2^5 × 5^5 × 5^2)/(5^7 ×〖 2〗^5 × 3^5 ) = 2^5/2^5 × 3^5/3^5 × 5^(5 + 2)/5^7 = 2^5/2^5 × 3^5/3^5 × 5^7/5^7 [(a × b)m = am × bm] [am × an = am + n] = 2^(5 − 5) × 3^(5 − 5) × 5^(7 − 7) = 2^0 × 3^0 × 5^0 = 1 × 1 × 1 = 1 [𝑎^𝑚/𝑎^𝑛 " = " 𝑎^(𝑚 − 𝑛) ]